Lemmus sibiricus Kerr 1792 - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
32. Siberian Brown Lemming Lemmus sibiricus French: Lemming de Sibérie / German: Sibirischer Lemming / Spanish: Lemming de Siberia Other common names: Black-footed Lemming, Brown Lemming, Ob Lemming, Siberian Lemming Taxonomy. Mus lemmus sibiricus Kerr, 1792, between Polar Ural Mountains and lower course of Ob River, Yamalo-Nenetskaya Nats. Okr., Russia. Lemmus sibiricus is closely related to L. lemmus and L. amurensis, and in captivity, they hybridize freely. Nevertheless, L. sibiricus consists of several deeply divergent evolutionary lineages. Genetic distances between the most divergent lineages (particularly between west-Siberian and eastSiberian) exceed divergence between west-Siberian lineage of sibiricus and L. lemmus. The idea that all these species are actually conspecific has a long history. The form portenkoi was classified as a separate species until very recently. Molecular assessments placed portenkoi and novosibiricus in the east-Siberian lineage, close to subspecies bungei. Lemmus sibiricus was reported as L. obensis in the past. Four subspecies recognized. Subspecies and Distribution. L.s.sibiricusKerr,1792—NEEuropeanRussia,NovayaZemlya,andW&CSiberiaasfarEasLenaRiver. L.s.bunge:Vinogradov,1925—ESiberiabetweenLenaandKolymarivers. L.s.novosibiricusVinogradov,1925—NewSiberianIs(NERussia). L. s. portenkoi Tschernyavsky, 1967 — Wrangel I (NE Russia). Descriptive notes. Head—body 99-160 mm, tail 8-17-6 mm; weight 49-120 g. Size is highly variable among and within populations of Siberian Brown Lemmings. They tend to be larger at high latitudes and smaller in taiga. They are very similar to Norway Brown Lemmings (L. lemmus) in external morphology and craniodental architecture, but their pelage is monochromatic. Back of the Siberian Brown Lemming is yellowish brown or rusty brown, and belly is whitish gray, with variable amount of buff tint. Black spinal stripe extends from neck to mid-back but is frequently interrupted or faint. Habitat. Flat moist Arctic tundra, with mires and bogs in lowlands and ...